2000
DOI: 10.1128/jvi.74.22.10287-10292.2000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Studies of a Recombinant Chimeric Respiratory Syncytial Virus FG Glycoprotein Vaccine in Cotton Rats

Abstract: Several formulations of a recombinant chimeric respiratory syncytial virus (RSV) vaccine consisting of the extramembrane domains of the F and G glycoproteins (FG) were tested in cotton rats to evaluate efficacy and safety. The FG vaccine was highly immunogenic, providing nearly complete resistance to pulmonary infection at doses as low as 25 ng in spite of inducing relatively low levels of serum neutralizing antibody at low vaccine doses. Upon RSV challenge animals primed with FG vaccine showed quite mild alve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Such pathology was first appreciated during clinical trials of a formalin-inactivated vaccine, which resulted in severely enhanced (and in some cases fatal) disease (2,6,12,13). The histopathologic changes seen in the two children who died in that study (23) are similar to those observed with other nonreplicating RSV vaccines (19,22), as well as those in the present report. Lingering concerns that novel nonreplicating RSV vaccines might also predispose to the development of proinflammatory immune-mediated lung pathology have cast a persistent shadow over RSV vaccinology.…”
Section: Discussionsupporting
confidence: 77%
“…Such pathology was first appreciated during clinical trials of a formalin-inactivated vaccine, which resulted in severely enhanced (and in some cases fatal) disease (2,6,12,13). The histopathologic changes seen in the two children who died in that study (23) are similar to those observed with other nonreplicating RSV vaccines (19,22), as well as those in the present report. Lingering concerns that novel nonreplicating RSV vaccines might also predispose to the development of proinflammatory immune-mediated lung pathology have cast a persistent shadow over RSV vaccinology.…”
Section: Discussionsupporting
confidence: 77%
“…However, enhancement was also found with the parainfluenza 3 vaccine inactivated by ultraviolet light [16]. Additionally, minor degrees of enhancement have been noted with a recombinant chimeric RSV FG glycoprotein and that effect was eliminated by a monophosphoral lipid A adjuvant which also reduces pathology of FI-RSV vaccine enhanced disease [19]. This adjuvant also had a dramatic effect in reducing both Th-1 and Th-2-type cytokines in a model of FI-RSV vaccine enhancement in cotton rats [4].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that infection of cotton rats with hMPV is associated with efficient viral replication in the lung and reproducible pulmonary pathology [10,28,30]. The cotton rat has also been used extensively to study hRSV especially in the area of enhanced pulmonary disease caused by some vaccine candidates for hRSV [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…131 Several RSV F, G and chimeric FG subunit vaccines have shown to be effective in rodent models, though only RSV F subunit vaccines have been extensively tested in humans. 51,81,132,133 Purified RSV F glycoproteins (PFPs) adjuvanted with alum were shown to exhibit an acceptable safety profile and to be immunogenic as measured by a ≥four-fold rise in RSV neutralizing antibody titers. PFP vaccines were generally more immunogenic in seropositive children than adults.…”
Section: Challenges For Developing a Pediatric Rsv Vaccinementioning
confidence: 99%